What makes a good phorophyte? Predicting occupancy, species richness and abundance of vascular epiphytes in a lowland seasonal tropical forest - Shen, Ting; Song, Liang; Collart, Flavien; Guisan, Antoine; Su, Yang; Hu, Hai-Xia; Wu, Yi; Dong, Jin-Long; Vanderpoorten, Alain (Frontiers in Forests and Global Change, 2022)
Epiphytes typically exhibit clustered distribution patterns, but predicting the spatial variation of their distribution at fine scales has long been a challenge. Taking advantage of a canopy crane giving access to 1.1 ha of lowland rainforest in Yunnan (China), we assess here which factors promote the probability that a given tree hosts epiphytes, and the variation of species richness and abundance of epiphytic spermatophytes and ferns among trees. Epiphytic spermatophytes and ferns occupied 2.3% and 10.8% of the available host trees, respectively. Significant models predicting which trees are more likely to host epiphytes than others were obtained, indicating that host tree characteristics and their local environment play a significant role in determining which host tree is most likely to be colonized. These models, as well as models for species richness and abundance, however, exhibited a moderate to low accuracy (r2 0.29 and 0.23 and of 0.13 and 0.17 for spermatophyte and fern species richness and abundance, respectively). This suggests that our inclusion of a large number of host-tree characteristics and their local environment did not allow for an apparent improvement of model accuracy over studies with a more limited number of predictors, pointing to the role of chance upon tree colonisation. The best predictor of the models was its DBH, confirming the utmost importance of large trees with emergent canopies for the conservation of the epiphytic flora. In ferns, however, two peaks of species richness were observed, representing shade-loving ferns on small trees and sun-loving ferns on large trees, suggesting that epiphytic diversity assessments must also include small understorey trees. Microclimatic conditions and light intensity were the best second factor best accounting for variation in species richness and abundance among trees. Given the importance of the micro-climatic conditions that prevail at the level of each individual host tree, the impact of the harvesting of trees in the vicinity of conserved individuals raises the question of the maintenance of suitable conditions at the level of isolated trees, pointing to the necessity to maintain a buffer zone around large host trees targeted for conservation.